1983
DOI: 10.1161/01.hyp.5.5.663
|View full text |Cite
|
Sign up to set email alerts
|

Opiate receptors and cardiovascular control in conscious SHR and WKY rats.

Abstract: SUMMARY This study examined the cardiovascular, respiratory, and sympathetic effects of selective fj. and 5 opioid agonists microinjected into the hypothalamic nucleus preopticus medialis (POM) of conscious SHR and WKY rats. The /x receptor agonist D-Ala -ol-enkephalin (DAGO) at a dose of 0.6 or 6.0 nanomoles (Nmol) increased the blood pressure and heart rate in WKY rats. In SHR rats, the lower dose of DAGO similarly had a pressor effect whereas the higher dose was depressor; heart rate was increased only by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Spontaneously hypertensive rats have been reported to show enhanced pressor responses to intracerebroventricular leucineenkephalin, 24 ]-enkephalin microinjected into the medial preoptic nucleus of the hypothalamus. 22 Moreover, the renal and mesenteric vasoconstrictions produced by intracerebroventricular DAGO were found to be significantly enhanced in SHR compared with WKY rats. 21 It is of some interest that the regional hemodynamic alterations produced by intracerebroventricular DAGO are similar to those produced by electrical stimulation of the PVH.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Spontaneously hypertensive rats have been reported to show enhanced pressor responses to intracerebroventricular leucineenkephalin, 24 ]-enkephalin microinjected into the medial preoptic nucleus of the hypothalamus. 22 Moreover, the renal and mesenteric vasoconstrictions produced by intracerebroventricular DAGO were found to be significantly enhanced in SHR compared with WKY rats. 21 It is of some interest that the regional hemodynamic alterations produced by intracerebroventricular DAGO are similar to those produced by electrical stimulation of the PVH.…”
Section: Discussionmentioning
confidence: 91%
“…20 In addition, the pressor responses to centrally administered opioid peptides were enhanced in SHR as compared with those in Wistar-Kyoto (WKY) rats. 22 " 25 Moreover, manipulation of food intake has been demonstrated to produce differential effects on systemic cardiovascular function between SHR and WKY rats. 26 - 27 Thus, in the present study, £-endorphin was microinjected into the PVH of SHR and WKY rats to elucidate a putative role for /3-endorphin as a neurotransmitter system integrating regulation of sympathoadrenal function by PVH neurons and a role of this system in the development of hypertension in SHR.…”
mentioning
confidence: 99%
“…17 In normotensive WKY, unlike the SHR, pronounced tachycardia accompanied the pressor response. 17 Studies still in progress in our laboratory have shown that the SHR also differ from WKY in their sensitivity to the distinct regional blood flow changes mediated by /nreceptors (Figure 1). The renal and mesenteric vasoconstriction produced by DAGO (0.1-10 nmol per rat i.c.v.)…”
Section: Pharmacological Evidencementioning
confidence: 98%
“…Administration of Z)-Ala2, McPhe4, Gly-ol5-enkephalin (D A M G O ), a highly selective ligand for p-opiate receptors, increases the blood pressure and heart rate in W K Y rats. In SH R rats, low doses of D A M G O produce pressor effects when in jected into the hypothalamic nucleus preopti cus medialis [5], D A M G O causes pressor re sponse when microinjected into nucleus ambiguus [6], The effects of opiate antagonists, naloxone and naltrexone on blood pressure have also been determined. Whereas in con scious squirrel monkeys, intravenous injec tions of naloxone or naltrexone (0.3-10 mg/kg) failed to affect blood pressure or heart rate [7], both agents in high doses produced a brief, dose-related decrease in mean arterial pressure of urethane-anesthetized SH R rats, but had no effect in W K Y rats [8], These effects of antagonists were suggested to be centrally mediated since quaternary com pounds which cross the blood-brain barrier with difficulty were ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have also been made to deter mine the effects of 5-opiate agonists on the cardiovascular system. D-Ala2, Z)-Leu5-enkephalin (DADLE) was shown to increase the systolic blood pressure, and the effect ap peared to be of greater intensity in SH R than in W K Y rats [5]. However, the relative distri bution of the central 8-opiate receptors in brain regions and spinal cord of W K Y and SH R rats is not known.…”
Section: Introductionmentioning
confidence: 99%